Evaluasi Kinerja Gudang sebelum dan setelah Perancangan Ulang Tata Letak: Studi pada PT Asta Nadi Karya Utama - Yoseph Sunardhi; Muhammad Dava Apriliansyah; Mora Berlianti Pangaribuan; Yohana Angelina Harefa (MANAJEMEN, 2026)
This study aims to evaluate the effectiveness of warehouse layout redesign on operational performance at PT Asta Nadi Karya Utama. The research method employs a quantitative approach with a before-after comparative analysis design. Data were collected through structured observation and performance measurements of 30 sample items during August–September 2025. Statistical analysis results show significant improvements in all performance indicators: item retrieval time decreased by 64.4% (from 8.03 minutes to 2.86 minutes, p < 0.001, d = 2.16), inventory accuracy increased by 20.0% (from 78.5% to 94.2%, p < 0.001, d = 1.32), vertical space utilization increased by 106.8% (from 35.2% to 72.8%, p < 0.001, d = 2.15), and operator productivity increased by 127.4% (from 18.6 to 42.3 items/hour, p < 0.001, d = 1.67). These findings confirm that layout redesign through zoning system implementation and vertical space optimization significantly improves warehouse operational efficiency.